(Ne)usvojeni cilji pravopisne zmožnosti v prvem vzgojno-izobraževalnem obdobju - Šek Mertük, Polonca (Revija za elementarno izobraževanje, 2017)
(Un)achieved Spelling Ability Objectives in the First Cycle of Basic School. Spelling ability is one of the basic communication abilities. Students begin to systematically develop with the beginning of school. By the end of the first cycle of basic school, students should achieve eleven operational objectives connected to spelling ability. There is a lack of studies dealing with the assessment of students’ achievement of spelling ability. The paper presents the state of (un)achieved spelling ability for the tested third graders. The results have given (future) teachers the insight into the state of spelling ability and consequently an opportunity to consider in further educating students on individual orthographic subjects.
Keywords: communication ability; spelling ability; Slovene course syllabus; first cycle of basic school; spelling ability objectives; standards of knowledge